Scrub typhus in third trimester of pregnancy: dilemmas in diagnosis and management - Jain, Geeta; Priyadarshani, Preeti; Sisodia, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Scrub typhus is an acute febrile illness rarely diagnosed in pregnancy. Here we report a case of scrub typhus in the third trimester of pregnancy, its associated complications and its management to ensure a favourable fetomaternal outcome. Mrs X, a 22- year old primigravida, was diagnosed with scrub typhus at 38 weeks of pregnancy after developing high- grade fever for 12 days. An atypical eschar was seen on one foot. Her ultrasonography revealed foetal tachycardia and severe oligohydramnios. She was started on tab azithromycin 500 mg OD but remained febrile even after two days. Fever subsided at dose of 1gm/day. When she was afebrile for 48 hours and adequately hydrated, labour was induced and she delivered vaginally a full-term alive baby of 2.2 kg. Vertical transmission was not observed in the baby. Scrub typhus is an easy-to-treat cause of acute undifferentiated febrile illness in the Indian subcontinent, and should always be a differential diagnosis even in the absence of a pathognomic eschar. Timely treatment ensures a favourable fetomaternal outcome.